Creep and Strength Behavior of Frozen Silt in Uniaxial Compression - Yuanlin, Zhu; Carbee, David L (1987)
Uniaxial constant-stress and constant-strain-rate compression tests were conducted on more than 200 remolded, saturated, frozen specimens of rates show a close strength correspondence between the constant-stress and constant-strain-rate tests. All of these complete stress vs strain rate curves could not be described by a single power law or exponential equation, indicating that different deformation mechanisms are dominant within different ranges of strain rate.